2018
DOI: 10.1186/s40317-018-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harness-attached tracking devices on survival, migration, and reproduction in three species of migratory waterfowl

Abstract: Background: Tracking devices have enabled researchers to study unique aspects of behavior in birds. However, it has become clear that attaching these devices to birds often affects their survival and behavior. While most studies only focus on negative effects on return rates, tracking devices can also affect the behavior under study, and it is therefore important to measure potential negative effects of tracking device attachment on the full range of behavioral aspects of birds. At the same time, we should aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…In the winter of 2008 and 2009, 15 female barnacle geese were captured using canon nets on their wintering grounds in the northwestern part of the province of Frysland, the Netherlands (53 37'N, 6 13'E) and fitted with PTT satellite transmitters (30 g) using cordura-nylon backpack harnesses [42]; 4 of them migrated to breeding grounds on the island of Kolguev between 2009 -2011 [53], which resulted in a total of 9 migration tracks included in this analysis. An analysis including data form both geolocators and GPS-loggers is feasible, as we found that migration timing and speed of birds with GPS-loggers did not differ from a control group equipped with geolocators [54].…”
Section: Migration Tracking Datamentioning
confidence: 94%
“…In the winter of 2008 and 2009, 15 female barnacle geese were captured using canon nets on their wintering grounds in the northwestern part of the province of Frysland, the Netherlands (53 37'N, 6 13'E) and fitted with PTT satellite transmitters (30 g) using cordura-nylon backpack harnesses [42]; 4 of them migrated to breeding grounds on the island of Kolguev between 2009 -2011 [53], which resulted in a total of 9 migration tracks included in this analysis. An analysis including data form both geolocators and GPS-loggers is feasible, as we found that migration timing and speed of birds with GPS-loggers did not differ from a control group equipped with geolocators [54].…”
Section: Migration Tracking Datamentioning
confidence: 94%
“…Individuals were colour‐ringed with unique codes, weighed within a few hours after capture, and sexed by cloacal examination. In total, 30 adult male brent geese were tagged with UvA‐BiTS GPS trackers (Bouten, Baaij, Shamoun‐Baranes, & Camphuysen, ), which were attached as a backpack using nylon strings inserted in 4‐mm wide silicon tubing (Lameris et al., ). Twenty‐one individuals were tagged at the pasture site and nine at the saltmarsh site.…”
Section: Methodsmentioning
confidence: 99%
“…In the summer of 2014, in the breeding colony of the Kolokolkova Bay, northern Russia (68°40'N, 52°17'E;van der Jeugd et al 2003), 40 incubating female Barnacle Geese were captured on their nests using spring-traps. UvA-BiTS GPS/accelerometer tags (19 g; Bouten et al 2013) were attached to these geese with Teflon backpack harnesses (Lameris et al 2017(Lameris et al , 2018a. GPS-data was remotely downloaded from 23 GPS/accelerometer tags in the summer of 2015 at the Kolokolkova Bay.…”
Section: Gps-datamentioning
confidence: 99%